A new delay parameter dependent on variable analysis periods at signalized intersections. Part 2: Validation and application - Akgüngör, Ali P. (Transport, 2008)
The main objective of the present study is to investigate the performance of the proposed model in Part 1 for variable demand, time and oversaturated conditions. To accomplish this objective and test the proposed model, an experimental study was performed. The proposed delay model for oversaturated traffic conditions was calibrated and verified by the TRAF‐NETSIM microscopic simulation program. In the calibration and verification of the proposed model, the simulation study was performed to produce various traffic and time conditions using 48 different scenarios. The delays obtained from the simulations and the proposed model were statistically compared using linear regression analysis. The results indicated that there was a good relationship R2 = 0.989 at 95 % confidence level between the delays generated by the simulations and the delays estimated by the proposed model.First published online: 27 Oct 2010